Enfermedad linfoproliferativa postrasplante de órgano sólido (2016)
ABSTRACT: Post-transplant lymphoproliferative disease (PTLD) is a group of disorders that may occur after transplantation. Its incidence is variable according to the transplanted organ. The clinical variability of this disease, its extra-nodal involvement and its broad histopathological spectrum make both classification and management very complex. This review provides an update about PTLD in patients with solid organ transplantation. Key words: Epstein-Barr Virus Infections; Lymphoproliferative Disorders; Organ Transplantation.